Analisis Keterkaitan Kualitas Pendidikan, Nilai Pelanggan di Sekolah Swasta Melalui Pendekatan Balanced Scorecard. - Elis Lisyawati; Khairunnisa; Edi Ruslani; Ade Ripai; Ade Tutty Rokhayati Rosa; Ida Tejawiyani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The use of the Balanced Scorecard method in performance measurement including determining teaching quality and customer value, allows assessment of financial aspects, customers, internal business processes, and learning and growth based on the goals that the organization has set. This measurement is based on the organization's stated goals, vision and mission. With the Balanced Scorecard, SMKN 2 Rangkasbitung obtained a comprehensive picture of its teaching quality and customer value, including the school's ability to fulfill the satisfaction of educational stakeholders. This research used a descriptive qualitative approach, with interview, observation and documentation techniques. Data analysis techniques recommended by Miles and Hubermen are data reduction, data presentation and conclusion drawing based on themes in the research. In the context of education, the Balance Scorecard serves as a guide to measuring and improving the performance of educational institutions comprehensively, and obtaining commitment from project participants and clarifying the framework for implementation and management that must be implemented after the preparation of the initial Balance Scorecad, as well as helping institutions to translate vision, mission into concrete actions through performance measurement from various perspectives and used to boost the organization's ability to multiply performance